Looking for a Place : The Third International Biennial - Grachos, Louis; Martinez, Rosa (Santa Fe : SITE Santa Fe, 1999)
Almeida, Helena ; Amer, Ghada ; Antoni, Janine ; Bonvicini, Monica ; Bourgeois, Louise ; Bruguera, Tania ; Cai Guo-Qiang ; Clark, Lygia ; Gatev, Dr. Galentin ; Greenpeace ; Gutiérrez, Yolanda ; Hatoum, Mona ; Hausswolff, Carl Michael von ; Höller, Carsten ; de Infante, Francisco Ruiz ; Kaern, Simone Aaberg ; Mthethwa, Zwelethu ; Navridis, Nikos ; Neshat, Shirin ; Neuenschwander, Rivane ; Orozco, Gabriel ; Rist, Pipilotti ; Sangar, Bülent ; Scofidio, Diller + ; Senchenko, Arsen Savadov & Georgy ; Teters, Charlene ; Vega, Sergio ; Yanagi Miwa
biografie
Looking for a Place : The Third International Biennial, SITE Santa Fe, July 10 - December 31, 1999
Engels
boek